Cohesion as a measure in generic analysis - Taboada, Maite (Círculo de Lingüística Aplicada a la Comunicación, 2023)
Cohesion, a property of any successful text, is also present in spoken language. Speakers relate their utterances to previous ones through the use of cohesive relations; a cohesive tie is established. Cohesive ties enter into cohesive chains, which run throughout a text, revealing how different parts of a text are related to each other. In this study I describe the results of an analysis of cohesive relations in a bilingual (English and Spanish) corpus of task-oriented dialogues. The two research questions I would like to address relate, first, to the relationship between the generic stages of the conversations and the boundaries of cohesive chains. The dialogues, as instances of a scheduling genre, proceed in clearly defined stages. I will show how cohesive chains are clearly related to stages in the dialogue. The second research question concerns measures of cohesive harmony in speech. The dialogues, although perfectly functional, seem to contain very low cohesive harmony. I suggest that different measures of cohesive harmony are necessary for different genres.